2010
DOI: 10.1111/j.1600-6143.2009.02986.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific Unwillingness to Donate Eyes: The Impact of Disfigurement, Knowledge and Procurement on Corneal Donation

Abstract: Although willingness, attitudes and beliefs surrounding solid-organ donation have been extensively investigated, much less is known about corneal donation. Despite evidence that a substantial number of families who agree to multiorgan donation also specifically refuse corneal donation, it is unclear why this occurs and what can be done to increase rates of corneal donation. We conducted a survey of 371 Australian adults regarding their views on corneal donation. Although willingness to donate corneas generally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
4
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 25 publications
(35 reference statements)
5
48
4
2
Order By: Relevance
“…These findings are in contrast with previous reports [5,[17][18][19][20][21][22]. For example, in 2001, Sundmacher and Reinhard reported in a local analysis a 30-50 % rate of acceptance regarding postmortem cornea donation in Germany [12].…”
Section: Discussioncontrasting
confidence: 82%
“…These findings are in contrast with previous reports [5,[17][18][19][20][21][22]. For example, in 2001, Sundmacher and Reinhard reported in a local analysis a 30-50 % rate of acceptance regarding postmortem cornea donation in Germany [12].…”
Section: Discussioncontrasting
confidence: 82%
“…(Table-II) 43.1%(195) of our participants thought that eye donation means removal of cornea which is similar to the study done by Ronaki et al(54.9%) . [9] 49.5 %( 224) knew that eye donation does not cause disfigurement as artificial prosthesis was given after collection of cornea which is similar to the study by Patil et al (39%), [6] Lawlor et al [19] and low in comparison to Ronaki et al (73.5%)and Bhandary et al(76.2%). [9,15] 43.1%(195)were aware that spectacle users,diabetics,hypertensives and post cataract surgery persons can donate their eyes, which is similar to the study of Ronaki et al(45.4%) .…”
Section: Discussionsupporting
confidence: 69%
“…With the increasing worldwide shortage of donor corneas for keratoplasty, there is a greater need to find a suitable substitute for donor corneas (15). As early as 2003, Amano et al suggested that heterogeneous corneal stromas, especially porcine corneal stromas, could be ideal alternatives to human corneas due to their lower antigenicities, as demonstrated in in vitro corneal tissue engineering, and transparently healing, as shown in animal experiments (16).…”
Section: Discussionmentioning
confidence: 99%